2022
DOI: 10.1186/s12974-022-02600-0
|View full text |Cite
|
Sign up to set email alerts
|

Impaired response of blood neutrophils to cell-death stimulus differentiates AQP4-IgG-seropositive NMOSD from MOGAD

Abstract: Background In neuromyelitis optica spectrum disorders (NMOSD) and myelin oligodendrocyte glycoprotein antibody-associated disease (MOGAD), neutrophils are found in CNS lesions. We previously demonstrated that NMOSD neutrophils show functional deficiencies. Thus, we hypothesized that neutrophil accumulation in the CNS may be facilitated by impairments affecting mechanisms of neutrophil death. Objective To evaluate cell death in blood neutrophils fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 72 publications
0
4
0
Order By: Relevance
“…The immunopathogenesis of neuromyelitis optica spectrum disorder (NMOSD) has been shown to involve many components of the adaptive immune system including T cells [ 1 , 2 ], B cells [ 3 ], monocytes [ 4 ], as well as the innate immune system, including complement [ 5 ], granulocytes [ 6 , 7 ], plasmablasts [ 8 ], and antibodies [ 9 ]. In a simplistic model, upstream communication among peripheral T cells, B cells and monocytes leads to a coordinated decision to attack the central nervous system.…”
Section: Introductionmentioning
confidence: 99%
“…The immunopathogenesis of neuromyelitis optica spectrum disorder (NMOSD) has been shown to involve many components of the adaptive immune system including T cells [ 1 , 2 ], B cells [ 3 ], monocytes [ 4 ], as well as the innate immune system, including complement [ 5 ], granulocytes [ 6 , 7 ], plasmablasts [ 8 ], and antibodies [ 9 ]. In a simplistic model, upstream communication among peripheral T cells, B cells and monocytes leads to a coordinated decision to attack the central nervous system.…”
Section: Introductionmentioning
confidence: 99%
“…Principal Component Analysis revealed that IL-8 was the top factor separating the NMOSD group from healthy controls. While a comprehensive analysis of cytokine levels in cerebrospinal fluid of NMOSD patients showed that IL-8 was significantly elevated compared to multiple sclerosis and controls 21 , another study using AQP4-IgG-positive NMOSD sera showed no significant elevation between healthy controls 22 . IL-8 is known www.nature.com/scientificreports/ as a chemotactic factor for granulocytes, mainly neutrophils, and also functions as a promoter of phagocytosis induction and angiogenesis 23 .…”
Section: Discussionmentioning
confidence: 95%
“… 38 , 47 Phagocytosis of apoptotic neutrophils is upregulated with the release of IL-10, and as they disintegrate due to their own apoptosis, they release a variety of lysosomal enzymes that lyse the surrounding tissue and form an abscess. 48 , 49 In addition to its anti-inflammatory effects, IL-10 has pro-inflammatory properties that can characterise aggressive inflammation by switching the function of regulatory B cells from inducing CD8 + T cell tolerance to inducing inflammatory CD4 + T cell responses. 50 In our study, IL-10 is a risk factor for GLM abscess formation, and the mechanism may be related to the induction of neutrophil apoptosis and increased inflammatory aggressiveness.…”
Section: Discussionmentioning
confidence: 99%